Identification Students’ Misconceptions of Class VIII SMPN 21 Padang in the Skeletal Systems of Organism by Using CRI Technique - Della Lestari; Dezi Handayani; Rahmawati Darussyamsu; Armen Armen (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Misconceptions that occur in science learning especially Biology will have a negative impact on students, both for learning outcomes or incompatibility in the process of application in the daily lives of students. This study discusses concepts and studies class VIII students of SMP 21 Padang in the academic year 2018/2019 which discusses misconceptions about the material systems of living motion. This research is a descriptive study conducted at SMP 21 Padang. The population of this research are 243 person students entering 2018/2019. The sample are 48 person was taken from 20% of the total participation. Sampling technique used cluster random sampling. The data used are primary data obtained through multiple choice tests obtained by Certainty Index Response (CRI) and analyzed quantitatively through percentages. Based on the results, the percentage of students’ misconceptions regarding the structure and function of muscle system 23.96%, the concept of plants movement 22.91%, the concept of structure and joint function 20.83%, skeletal system 19.44%, disorders of system 18.75 %, the concept of animals movement 15.62%